Convergence analysis of a two-point gradient method for nonlinear ill-posed problems. (1st August 2017) - Hubmer, Simon; Ramlau, Ronny
Abstract: We perform a convergence analysis of a two-point gradient method which is based on Landweber iteration and on Nesterov's acceleration scheme. Additionally, we show the usefulness of this method via two numerical example problems based on a nonlinear Hammerstein operator and on the nonlinear inverse problem of single photon emission computed tomography.